Kekuatan Geser Panel Kayu Vertikal Dengan Perkuatan Single Bracing Tulangan Baja Akibat Pembebanan Siklik - Fanny Monika (Universitas Muhammadiyah Yogyakarta, 2016)
Panels in wooden construction serve as walls as well as providing structural lateral resistance against earthquake if designed well. Panel materials consist of frames with sheathings such as Plywood or Oriented Strand Board(OSB) connected to wooden frames with nails as connectors. Lateral force of the panels can be increased, for example by adding diagonal rods/bracings to the frames. In this study a wooden panel which was Sengon wooden panel connected to Laminated Veneer Lumber(LVL) wooden panel with CN 50 nails with a diameter of 2,8 mm and the distance between the nails was 240 mm with plain steel reinforcement single bracing with a diameter of 8 mm in pull position using corner plate as a connector between bracing and LVL wooden panel. Cyclic test had 20%Δy, 40%Δy, 60%Δy deformation controls and loaded with monotonic until wooden panels collapsed. The results of cyclic test in stable condition 60%Δy had equivalent viscous damping ratio values of 8,324%. Failures in panels often happened to connecting nails, corner plates, and steel bracings. The types of failure were Nail Pull-Through of Sheathing, Pull-Through Sheathing Failures, Mudsill Failure, buckling on corner plates, and buckling on steel bracings